Applying Technology Acceptance Model to measure online student residential management software acceptance - Siwale, Maka (2022)
The purpose of this study is to apply the technology acceptance model developed by Davis (1989) to examine the acceptance of online-based Student Residential Management Software by university on-campus housing student residents. The study examines students’ experience of using online-based software, which is believed to influence the perceived ease of use, the perceived usefulness, and the behavioural intention to use such software. The results of this study were then compared to the findings of other past studies that had applied and/or tested TAM. The study participants were selected from a university in Western Australia that had implemented Student Residential Management Software and had used it for about two semesters. A total of 227 valid questionnaires were collected, and structural equation modelling was conducted to examine the research hypotheses. The findings provide practical implications for university residential administrators and the developers and designers of residential management software for students. Further, from a theoretical perspective, this study highlights the confirmation of the technology acceptance model in the context of student residential housing management.